PENGUKURAN BEBAN KERJA MENTAL DAN FISIK PADA PROSES PENGECEKAN KECATATAN PIPA - Arnes Faradilla; Pudji Astuti; Muhammad Ihza Alayvrin (KAIZEN : Management Systems & Industrial Engineering Journal, 2022)
The workload in ergonomics is divided into two parts, namely the mental load and the physical load. The mental load is a workload related to cognitive, perception, and concentration, while the physical load is related to human physical activity. The pipe checking process carried out by 3 operators at PT Bakrie Pipe Industries requires high concentration. This operator must check for pipe defects which are done for 8 hours per day and are repetitive. The purpose of this study was to measure the mental and physical load on operators using NASA TLX and energy consumption methods. This research was conducted starting with observing and interviewing the operator, then distributing the NASA TLX questionnaire and measuring the pulse. The results showed that the three operators had a high mental and physical burden, especially operator 3 who was older than the other operators. There is a relationship between age and the activities carried out so that it can cause differences, although not too significant. The need for immediate repairs in this work is due to manual work to check pipe defects without any tools, causing excessive stress and fatigue to the operator.